2000
DOI: 10.1001/archpsyc.57.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Change in Early Phase Schizophrenia During 12 Months of Treatment With Olanzapine, Risperidone, or Haloperidol

Abstract: These data suggest that olanzapine has some superior cognitive benefits relative to haloperidol and risperidone. A larger sample replication study is necessary to confirm and generalize the observations of this study and begin evaluation of the implications of this change to cerebral function and quality of life for people with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
255
5
6

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(278 citation statements)
references
References 44 publications
11
255
5
6
Order By: Relevance
“…26, NO. 5 Antipsychotics and Hippocampal Acetylcholine 589 olanzapine and clozapine, and to some extent risperidone, have been found to be beneficial in improving procedural learning tasks; these cognitive improvements have not been apparent with haloperidol treatment (Purdon et al 2000;Purdon 2000). All experiments in the present study were conducted in the presence of 0.3 M of the AChesterase inhibitor neostigmine in the perfusion solution.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…26, NO. 5 Antipsychotics and Hippocampal Acetylcholine 589 olanzapine and clozapine, and to some extent risperidone, have been found to be beneficial in improving procedural learning tasks; these cognitive improvements have not been apparent with haloperidol treatment (Purdon et al 2000;Purdon 2000). All experiments in the present study were conducted in the presence of 0.3 M of the AChesterase inhibitor neostigmine in the perfusion solution.…”
Section: Discussionmentioning
confidence: 96%
“…**p Ͻ .01, ***p Ͻ .001 compared with the respective vehicle. olanzapine and clozapine, and to some extent risperidone, have been found to be beneficial in improving procedural learning tasks; these cognitive improvements have not been apparent with haloperidol treatment (Purdon et al 2000;Purdon 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the procognitive effects of atypical relative to typical antipsychotics has indicated somewhat greater benefit with atypical compared with typical antipsychotics (Bilder et al, 2002;Green et al, 2002;Harvey et al, 2000;Keefe et al, 1999;Purdon et al, 2000). In general, modest cognitive benefits from antipsychotic medications are characterized by reduction of generalized cognitive deficits across a wide range of abilities, rather than particular effects on a specific neuropsychological domain (Buchanan et al, 1994;Cassens et al, 1990;Hill et al, 2004a;Rollnik et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among the advantages of these 'second-generation' antipsychotics (SGAs) (also referred to as 'atypical' or 'modern' antipsychotics) over 'first-generation' antipsychotics (FGAs) (also referred to as 'typical', 'traditional', or 'conventional' antipsychotics) are reduced extrapyramidal side effect profiles (Rosenheck et al, 1997;Simpson and Lindenmayer, 1997), reduced risk for tardive dyskinesia (Chouinard, 1995;Lieberman et al, 1994), greater effects on the negative and positive symptoms (Kane et al, 1988;Marder and Meibach, 1994;Beasley et al, 1996), and possibly beneficial effects on cognitive functioning (Purdon et al, 2000;Harvey et al, 2003;Bilder et al, 2002). SGAs have diverse receptor profiles, and the mechanism of action is still controversial (Seeman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In early randomized controlled trials, risperidone was found to be superior to haloperidol with regard to verbal working memory and verbal declarative memory (Kern et al, 1999). A randomized clinical trial of Purdon et al (2000) compared cognitive effects of haloperidol with two SGAs (olanzapine and risperidone) over 12 months and found olanzapine to be superior to risperidone and haloperidol in a global cognitive measure, with few reliable treatment differences for single tests or cognitive domains. This study has been criticized for high dropout rates, which were different between treatments (Weiss et al, 2002), and for a high average dosage of risperidone (Sharma, 2002).…”
Section: Introductionmentioning
confidence: 99%